Refusal strategies in English by Malay University students. - Hiba Qusay Abdul Sattar,; Salasiah Che Lah,; Raja Rozina Raja Suleiman, (Penerbit UKM, 2011)
Refusals, like other speech acts, occur in all languages. According to Searle (1969), all linguistic communication involves the production of speech acts, such as offering apologies, asking questions, making promises, or refusing. The speech act of refusal has been looked at by many researchers. However, in the Malaysian context, the study of refusals has yet to be ventured, either focusing on manifestations in the speaker’s mother tongue, or focusing on manifestations in English. This study aims to discover the preferred semantic formulas or strategies used by Malay university students in Malaysia to refuse a request in an academic context. For this study, 40 undergraduate and postgraduate students were asked to respond to different situations in which they were required to carry out the speech act of refusing a request. The data, collected by means of a Discourse Completion Test, were analyzed in terms of semantic formulas and were categorized according to the refusal taxonomy of Beebe et al. (1990). The findings show that participants differ in the ways they perform refusals. Regret or saying ‘sorry’, and giving excuses or explanations were the preferred formulas used in refusing requests. The choice of these semantic formulas suggests the influence of Malay culture in respondents’ realizations of refusals in English.